SUBJECT AND AUTHOR INDEXS - Volume 2, IJBE (Indonesian Journal of Business and Entrepreneurship, 2016)
SUBJECT INDEX IJBE VOLUME 2 access credit, 93 acquisition, 177 AHP, 61, 82, 165 arena simulation,43 BMC, 69 Bojonegoro, 69 brand choice, 208 brand image, 208 brand positioning, 208 bullwhip effect, 43 burger buns, 1 business synergy and financial reports, 177 capital structure, 130 cluster, 151 coal reserves, 130 coffee plantation, 93 competitiveness, 82 consumer behaviour, 33 consumer complaint behavior, 101 cooking spices, 1 crackers, 1 cross sectional analytical, 139 crosstab, 101 CSI, 12 direct selling, 122 discriminant analysis, 33 economic value added, 130, 187 employee motivation, 112 employee performance, 112 employees, 139 EOQ, 23 farmer decisions, 93 farmer group, 52 financial performance evaluation, 187 financial performance, 52, 177 financial ratio, 187 financial report, 187 fiva food, 23 food crops, 151 horticulture, 151 imports, 151 improved capital structure, 177 IPA, 12 leading sector, 151 life insurance, 165 LotteMart, 43 main product, 61 marketing mix, 33, 165 matrix SWOT, 69 MPE, 61 multiple linear regression, 122 muslim clothing, 197 Ogun, 139 Pangasius fillet, 82 Pati, 93 pearson correlation, 101 perceived value, 208 performance suppy chain, 23 PLS, 208 POQ, 23 portfolio analyzing, 1 product, 101 PT SKP, 122 pulp and papers, 187 purchase decision, 165 purchase intention, 33 remuneration, 112 re-purchasing decisions, 197 sales performance, 122 sawmill, 52 SCOR, 23 sekolah peternakan rakyat, 69 SEM, 112 SERVQUAL, 12 Sido Makmur farmer groups, 93 SI-PUHH Online, 12 small and medium industries (IKM), 61 socio-demographic, 139 sport drink, 208 stress, 139 supply chain, 43 SWOT, 82 the mix marketing, 197 Tobin’s Q, 130 trade partnership, 52 uleg chili sauce, 1 AUTHOR INDEX IJBE VOLUME 2 Achsani, Noer Azam, 177 Andati, Trias, 52, 177 Andihka, Galih, 208 Arkeman, Yandra, 43 Baga, Lukman M, 69 Cahyanugroho, Aldi, 112 Daryanto, Arief, 12 David, Ajibade, 139 Djoni, 122 Fahmi, Idqan, 1 Fattah, Muhammad Unggul Abdul, 61 Hakim, Dedi Budiman, 187 Harianto, 93 Hartoyo, 101 Homisah, 1 Hubeis, Musa, 112 Hutagaol, M. Parulian, 93 Jaya, Stevana Astra, 93 Juanda, Bambang, 52 Kirbrandoko, 122, 208 Manurung, E. Batara, 130 Mukhlis Yusuf, Ahmad, 1 Najib, Mukhamad, 165, 197 Noor Yuliati, Lilik, 208 Nugraha, Artadi, 23 Nuryartono, Nunung, 151 Oktaviani, Rina, 122 Prasetyo, Andrie, 101 Primadona, Fitry, 165 Qaulan Tsaqiela, Bimahri, 43 Ramadhan, Arfin, 82 Ridho Nurrochmat, Dodik, 33 Rifin, Amzul, 23, 151 Rusolono, Teddy, 12 Sanim, Bunasor, 43 Saptono, Imam Teguh, 130 Satria, Arief, 61 Setiawan, Indarto, 197 Simanjuntak, Mangatas, 12 Siregar, Hermanto, 130 Suharjo, Budi, 197 Sukandar, Dadang, 187 Sukardi, 23 Sumarwan, Ujang, 33, 165 Suprayitno, Gendut, 61 Suwandi, Ruddy, 82 Syahran, Rinaldi, 187 Syarief, Rizal, 69 Tinaprila, Netti, 101 Trilaksani, Wini, 82 Ulfah, Iffatul, 33 Wahyudi, Imam, 151 Widyatami, Sarah, 52 Wijayanto, Hari, 112 Wiska, Friesgina, 69 Zen, Novian, 177